Aplikasi Alat Pengendali Wereng Berbasis Solar Cell Di Desa Bringin Kabupaten Malang - Eddy Suprihadi; Bayu Firmanto; taufik kurrahman (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Planthopper attacks often occur suddenly in the Bringin village, Malang Regency. Efforts to spray using pesticides to eradicate plant hopper attacks have been carried out, but this method is less effective due to sporadic flying ability when spraying. For this reason, an integrated pest control technique is needed in addition to using pesticides so that pest control can be carried out effectively. The Community Partnership Program aims to help farmers overcome planthopper pests in rice fields by using pest traps based on solar cell technology. The method used in the implementation of this partnership program is to provide training in integrated pest control techniques and the manufacture of prototypes of planthopper pest control based on solar cell technology, and assistance to partner farmer groups during the application of tool technology in paddy fields to monitor the effectiveness of the use of tools to control pests leafhopper. The results of the program's implementation are indicated by the installation of four units of planthopper exterminator in one of the partner's paddy fields as the location of the demonstration plot. The results of using solar cell-based pest traps on land during the dry season showed that the tool was not only able to kill the planthopper but was also effective in trapping other pests that were flying around the location of the demonstration plot. It is hoped that after the implementation of the partnership program it can motivate other farmers to implement integrated pest management that is environmentally friendly